Pengaruh Motivasi Belajar terhadap Prestasi Belajar Matematika Siswa Kelas X SMA Negeri 3 Sibolga T.A 2021/2022 - Adi Suarman Situmorang; Handoko Priono H.S; Simon M. Panjaitan (Departement of Mathematics Education, 2023)
This study aims to determine the effect of motivation on mathematics learning achievement of class X students of SMA Negeri 3 Sibolga T.A 2021/2022. The influence of learning motivation on students is very important, because it can improve learning outcomes well through the achievements obtained. The results of observations and observations made by the author show that there are still many students who are still lacking in mathematics learning achievement who are involved in paying attention to the teacher explaining learning directly, focus and self-confidence are still lacking due to a lack of interest in learning mathematics. However, this can be prevented by applying the influence of learning motivation on students, especially in learning mathematics so that they are always active and enthusiastic in undergoing education in order to obtain good learning achievements. The effect of motivation is very important because it can encourage self-awareness to focus on the desired goal.